Granulomatous inflammation in inborn errors of immunity - Sacco, Keith A.; Gazzin, Andrea; Notarangelo, Luigi D.; Delmonte, Ottavia M. (Frontiers in Pediatrics, 2023)
Granulomas have been defined as inflammatory infiltrates formed by recruitment of macrophages and T cells. The three-dimensional spherical structure typically consists of a central core of tissue resident macrophages which may merge into multinucleated giant cells surrounded by T cells at the periphery. Granulomas may be triggered by infectious and non-infectious antigens. Cutaneous and visceral granulomas are common in inborn errors of immunity (IEI), particularly among patients with chronic granulomatous disease (CGD), combined immunodeficiency (CID), and common variable immunodeficiency (CVID). The estimated prevalence of granulomas in IEI ranges from 1-4%. Infectious agents causing granulomas such Mycobacteria and Coccidioides presenting atypically may be ‘sentinel’ presentations for possible underlying immunodeficiency. Deep sequencing of granulomas in IEI has revealed non-classical antigens such as wild-type and RA27/3 vaccine-strain Rubella virus. Granulomas in IEI are associated with significant morbidity and mortality. The heterogeneity of granuloma presentation in IEI presents challenges for mechanistic approaches to treatment. In this review, we discuss the main infectious triggers for granulomas in IEI and the major forms of IEI presenting with ‘idiopathic’ non-infectious granulomas. We also discuss models to study granulomatous inflammation and the impact of deep-sequencing technology while searching for infectious triggers of granulomatous inflammation. We summarize the overarching goals of management and highlight the therapeutic options reported for specific granuloma presentations in IEI.